THE CHARACTERIZATIONS OF MISS TRUNCHBULL AS ANTAGONIST IN ROALD DAHL’S MATILDA - Larassati, Ni Putu Sienna Diva; Suwastini, Ni Komang Arie; Artini, Ni Nyoman; Minxia, Zhu; Farlina, Nina (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The present study examines the antagonist in Roald Dahl’s Matilda, namely Miss Trunchbull. While previous studies focused on feminist and moral values of the protagonist, limited attention has been addressed to the antagonist’s role in shaping narrative conflict. The present study employed interpretive qualitative approach to analyze Miss Trunchbull’s traits and her role an antagonistic force in the novel. Through close reading and interactive qualitative data analysis model by Miles, Huberman, and Saldana, the findings reveal that Miss Trunchbull functions as the primary source of conflict, oppression, and fear that drives the narrative forward. Her characterizations, namely rude, authoritarian, arrogant, intimidating, malevolent, cunning, disciplined, and sturdy obstruct the protagonist’s development. The present study contributes to children’s literature criticism by highlighting the ideological significance of antagonistic characters in literary studies.